Synthesis and physicochemical characterization of three newly synthesized sulfhydroxamic acid derivatives as potential dual inhibitors of cyclooxygenase-2 and 5-lipoxygenase enzymes - Bošković, Jelena; Čudina, Olivera; Dobričić, Vladimir (Archives of Pharmacy, 2022)
Inflammatory mediators derived from arachidonic acid by the enzymes cyclooxygenase (COX) and lipoxygenase (LOX) are involved in the pathogenesis of various inflammatory diseases. Inhibition of the COX pathway is thought to lead to potentiation of the LOX pathway, and inhibition of both pathways represents a rational approach to the design and development of more effective and safer anti-inflammatory drugs. The aim of this study was the synthesis and physico-chemical characterization of 1f, 1g and 1h derivatives derived from a previously conducted 3D-QSAR study and molecular docking. The sulfhydroxamic acid derivative 1f was synthesized in a two-step process. Sulfonyl chloride was synthesized from commercially available sulfonic acid and thionyl chloride in the presence of a catalytic amount of DMF. Sulfhydroxamic acid was further obtained from previously synthesized sulfonyl chloride and hydroxylamine hydrochloride in the presence of 10% NaHCO3 solution. Sulfhydroxamic acid derivatives, 1g and 1h were synthesized from commercially available sulfonyl chlorides and hydroxylamine hydrochloride in the presence of 10% NaHCO3 solution. The reaction mixtures were purified by liquid-liquid extraction and preparative TLC to give derivatives 1f, 1g, 1h in yields: 26%, 53% and 63%. The structure and purity of the synthesized compounds were confirmed by determination of the melting points and spectroscopic techniques (ATR-FTIR, 1H-NMR, 13C-NMR, MS/MS). Based on a previously conducted in silico study, the voluminous sulfhydroxamic group is responsible for iron chelation within 5-LOX active center and for COX-2 selectivity, as COX-2 has wider side pocket, so potent inhibition of COX-2 and 5-LOX enzymes is expected.